Resin yield of Pinus nigra and Pinus sylvestris in the Slovenian Karst - Domen Gajšek; Miha Brecelj; Kristjan Jarni; Robert Brus (Acta Silvae et Ligni, 2018)
The aim of our research was to study the impact of various environmental factors on the resin production of pines in the Slovenian Karst. Five plots were established % three in Pinus nigra (Arnold) stands and two in Pinus sylvestris (L.) stands. On each plot, the 19-20 most vigorous dominant or codominant trees with a minimum diameter at breast height (DBH) of 20 cm were selected and their resin yield analysed in 2012. Resin yield in P. nigra was considerably higher than that in P. sylvestris. The average resin yield per tree during the study period of 102 days was 1.144 kg for P. nigra and 0.612 for P. sylvestris. There were substantial differences in resin yield among individual trees in the study period: 0.336-2.487 kg for P. nigra and 0.249-1.270 kg for P. sylvestris. The resin yield in P. nigra was considerably higher for the trees with larger DBH, while this was not the case in P. sylvestris. Tree species was the most important factor in resin yield. Increased precipitation resulted in higher resin yields on most plots, whereas better site productivity positively affected resin yield on all P. nigra plots but not on P. sylvestris plots.